A study of knowledge and behaviour regarding blood donation among medical college students of Ajmer, Rajasthan, India - Meharda, Bharat; Keswani, Mahesh; Choudhary, Pradeep Kumar; Mehra, Ankit (International Journal Of Community Medicine And Public Health, 2019)
Background: Blood is specialized body fluid in humans that delivers necessary substances such as nutrients and oxygen to the cells and transports metabolic waste products away from that same cells. Methods: The study was conducted among undergraduate medical students of J.LN. Medical College, Ajmer, Rajasthan, India in March 2019. It was a descriptive cross‑sectional study among 1st professional MBBS students. Results: The study participants included age range of 17-20 years. 96 (78.04%) study participants were knows blood group “O” is a universal donor and 94 (76.42%) were know blood group “AB” is universal recipient. majority of study participants 48 (45.28%) not donate due to fear of procedure. Conclusions: Role of health care personnel and medical students of a medical college for blood donation are pivotal.